Answer:
A. (f-g)(x) = -7x -3
Step-by-step explanation:
(f -g)(x) = f(x) -g(x) = (-3x -5) -(4x -2)
= -3x -5 -4x +2
= -3x -4x -5 +2
(f -g)(x) = -7x -3
Answer:
I would need to see an actual table to answer this question.
Y=-2(x-4)^2-6
The -6 makes it shift from origin(0,0) to (0,-6)
Then the -4 inside with x, makes it shift to the right by for, so the center would be now instead of (0,0), (4,-6).
As it has a negative A factor, it is a parabola open downwards, so the center is the maximum value.
Answer: (4,-6)
Hope you get it!
Answer:
the answer is X<5/3 correct me if i'm wrong
Step-by-step explanation:
hope this helps
Answer:
6x - 15
Step-by-step explanation:
f(x) = 2x + 3 and g(x) = 3x - 9.